KALIMAT TANYA DALAM BAHASA INGGRIS DAN BAHASA KARO SUATU ANALISIS KONTRASTIF - SEMBIRING, JUWITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT  This study is an attempt to identify, classify, analyze and contrast the English and Karo language which focuses on the interrogative sentences in relation to their forms and functions.  The writer analyzed interrogative sentences based on the concept of Quirk (1985), and contrasted them by using Lado’s theory (1957).  The Karo language data were two hundred and fifty items as the English data were one hundred and forty items. The result showed that interrogative sentences in English and Karo language have similarity in form and function. English has three forms of interrogative sentences such as yes-no question, wh-question and alternative question and Karo language has three question forms such as yes-no question, wh question (Kai, ija, engkai, isai, ndigan, uga, siapai, kuja) and alternative question. Keywords: English, Karo language, interrogative sentence, contrast